CERDIK Meningkatkan Pengendalian Penyakit Tidak Menular di Indonesia: Systematic Review - Hamdan Hariawan; Diana Pefbrianti (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2020)
Introduction: Non-Communicable Diseases (NCD) is the highest cause of death in Indonesia. The increase in non-communicable diseases prevalence is related to unhealthy lifestyles, including smoking, consumption of alcoholic beverages, lack of physical activity, and consumption of fruits and vegetables. CERDIK is a form of Indonesia government activity program to improve the prevention and management of non-communicable diseases. CERDIK consists of a series of health check activities, building non-smoking or smoking cessation behavior, diligent physical activity, a balanced diet, adequate rest, and being able to manage stress. This review literature aims to provide an overview of the effectiveness of CERDIK in efforts to improve non-communicable diseases control in Indonesia. Methods: The method used in this systematic review began with the selection of topics, then the keyword was determined to search for journals using English through several databases, including Science direct, Ebscho, Pro-Quest, and Google Scholar. Results: 6 articles mentioned that CERDIK was effective in increasing non-communicable diseases prevention and control behavior both in terms of cognitive, attitude and skills. While 2 other articles mention the successful implementation of the government program "CERDIK" in the field in controlling non-communicable diseases. Conclusion: The CERDIK program is effective in increasing non-communicable diseases control. Keywords: CERDIK; effectivity; non-communicable diseases ABSTRAK Pendahuluan: Penyakit Tidak Menular (PTM) menjadi penyebab kematian tertinggi di Indonesia. Kenaikan prevalensi PTM ini berhubungan dengan pola hidup yang tidak sehat, antara lain merokok, konsumsi minuman beralkohol, aktivitas fisik yang kurang, serta konsumsi buah dan sayur yang kurang. CERDIK adalah salah satu bentuk program kegiatan pemerintah untuk meningkatkan pencegahan dan penatalaksanaan penyakit tidak menular. CERDIK terdiri dari rangkaian kegiatan cek kesehatan, membangun perilaku tidak merokok atau berhenti merokok, rajin aktivitas fisik, diet seimbang, istirahat yang cukup, dan mampu mengelola stre. Tujun literatur review ini untuk memberikan gambaran mengenai efektivitas CERDIK dalam upaya meningkatkan pengendalian PTM di Indonesia. Metode: Metode yang digunakan dalam systematic review ini diawali dengan pemilihan topik, kemudian ditentukan keyword untuk pencarian jurnal menggunakan Bahasa Inggris melalui beberapa database antara lain Science direct, Ebscho, Pro Quest dan google scholar. Hasil: 6 artikel menyebutkan CERDIK efektif dalam peningkatan perilaku pencegahan dan pengendalian PTM baik dari segi kognitf, sikap, maupun keterampilan. Sedangkan 2 artikel lainnya menyebutkan keberhasilan pelaksanaan program pemerintah “CERDIK” di lapangan dalam pengendalian PTM. Kesimpulan: program CERDIK efektif dalam meningkatkan pengendalian PTM. Kata kunci: CERDIK; efektivitas; penyakit tidak menular